Long‐Term Survival Rates of Patients with Stage III–IV Hodgkin Lymphoma According to Age, Sex, Race, and Socioeconomic Status, 1984–2013. (8th May 2018) - Li, Yushi; Sun, Huanhuan; Yan, Yan; Sun, Tiantian; Wang, Shuncong; Ma, Haiqing
Abstract: Background: Long‐term survival rates for patients with stage III–IV Hodgkin lymphoma, or advanced Hodgkin lymphoma (aHL), have increased substantially since the 1960s. Because large‐scale research of aHL is rare, we aimed to demonstrate the differences in incidence and survival of aHL according to four patient variables in recent decades, with a focus on the outcomes of treatment of aHL and the advancement of public health care. Materials and Methods: Data on aHL cases diagnosed during 1984–2013 were extracted from the Surveillance, Epidemiology, and End Results Program database. Relative survival, Kaplan‐Meier, and Cox proportional hazards regression analyses were performed to identify prognosis indicators for aHL. Results: The incidence rates for aHL were 1.1, 0.8, and 1.0 per 100, 000 in the first, second, and third decades, respectively, during 1984–2013. The 120‐month relative survival rate improved continuously in each decade from 58.5% to 64.6% to 72.1%. In addition, disparities in the 120‐month relative survival rate between male and female patients and among patients of different races narrowed over time. The difference in long‐term survival rate between the poor (medium and high poverty) and rich (low poverty) groups narrowed across the 3 decades. Conclusion: The long‐term survival rate for patients with aHL increased in each decade, whereas survival rate disparities according to sex, race, and socioeconomic status narrowed, except for older patients aged >60 years and the high‐poverty group. Implications for Practice: Long‐term survival rates of patients with advanced Hodgkin lymphoma were elaborated in this article. The disparities according to sex, race, and socioeconomic status of survival condition were analyzed and showed the development of the public health care system and modern medicine technology. Abstract : This article examines interpatient differences in advanced Hodgkin lymphoma incidence and long‐term survival using data from the SEER database. Socioeconomic status and racial heterogeneities in the U.S. health care system have drawn increasing attention from oncologists and epidemiologists; therefore, whether a patient's sex, age, race, and socioeconomic status affect incidence rate and long‐term survival is a focus.